Effectiveness of Over-the-Counter Nicotine Replacement Therapy: A Qualitative Review of Nonrandomized Trials - Hughes, John R. (Oxford University Press, 2011)
AIM: Randomized trials conducted in over-the-counter (OTC) settings have shown that nicotine replacement therapy (NRT) is effective. This paper reviews nonrandomized tests of the effectiveness of OTC NRT. METHODS: Literature search via computer and other methods located (a) retrospective cohort studies of users versus nonusers of OTC NRT and (b) studies of quit rates before versus after NRT went OTC or before versus after NRT was given free to quitline callers. The methods were too heterogeneous to allow meta-analysis. RESULTS: The results were similar for cohort and pre- versus post-studies. Most of the studies found numerically greater quitting among NRT users than nonusers. Often when NRT was not found effective, other assumed effective treatments (e.g., phone counseling) were also not found effective, suggesting biased or insensitive study methods. Only about half of the studies found statistically greater quitting among NRT users, and the most rigorous studies did not find greater quitting among users. Many studies found selection bias, for example, NRT users are more dependent smokers. CONCLUSIONS: Some lines of evidence appear to confirm the effectiveness of OTC NRT, but others do not. We believe further secondary analyses using nonrandomized comparisons are unlikely to resolve this issue due to sensitivity, specificity, and selection bias problems.